2023
DOI: 10.3390/ani13081280
|View full text |Cite
|
Sign up to set email alerts
|

Where Are We Now? Feeds, Feeding Systems and Current Knowledge of UK Horse Owners When Feeding Haylage to Their Horses

Abstract: Despite our improved understanding of equid digestive health and accurate rations formulations, obesity in the UK horse population remains high. Study aims: (1) to determine how owners are feeding their horses and what influences their choices, (2) to understand owners’ knowledge of haylage and (3) to identify key areas that require additional education. Data were collected in 2020 from 1338 UK horse owners via two online surveys. Survey 1 (S1) was on general feeding practices, and Survey 2 (S2) was specifical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…This percentage closely aligns with the 14% reported in the present study. Notably, a comparable proportion of respondents in the previous study (16%) and in the current work (20%) were unaware of the practice of forage analysis [ 61 ]. It is important to note that the previous research targeted all UK horse and pony owners, whereas the current study specifically to evaluate owners of native-breed type ponies in Scotland.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…This percentage closely aligns with the 14% reported in the present study. Notably, a comparable proportion of respondents in the previous study (16%) and in the current work (20%) were unaware of the practice of forage analysis [ 61 ]. It is important to note that the previous research targeted all UK horse and pony owners, whereas the current study specifically to evaluate owners of native-breed type ponies in Scotland.…”
Section: Discussionmentioning
confidence: 91%
“…Research has identified a high degree of variability in the results of preserved forage analyses [ 60 ], indicating that multiple samples are required from each batch taken for the most representative results. In a survey of 613 UK horse owners who fed haylage, only six out of the twenty-nine who paid for an analysis did so with every batch [ 61 ]. This suggests that it may be uncommon for analysis of forage to be undertaken with great frequency, perhaps attributable to high preserved forage bale turnover, such as on livery yards or where owners feed a large number of horses.…”
Section: Discussionmentioning
confidence: 99%